Challenges of economic development in the Middle East and North Africa region - Devlin, Julia 1966- (World Scientific studies in international economics, 2010)
This important book surveys major economic issues in the development of countries in the Middle East and North Africa (MENA) region since World War II. It reviews the key challenges facing the region in moving towards greater market orientation and integration with the global economy. It also incorporates a discussion of tools and methods used by development practitioners and briefly examines issues of aid effectiveness. Topics covered include patterns of growth, economic reform strategies, the role of OPEC and oil in development, water scarcity and agricultural policies, population, education.